(untitled) (Al-Qamar, 2019)
It is generally observed that educational system of Pakistan is not producing the individuals required for the progress and prosperity of Pakistan. In spite of having highly talented young generation, having bulks of natural resources, Pakistan is lagging far behind in global race. When we think over the reason behind it, we come to know that each field of our educational system is badly affected rather pledged with the policies of British Empire. It is, no doubt, a serious matter. Governments must take it serious and work upon it. In this situation, the first thing is to mention and indicate the impact of orientalism on our educational system, specifically on the syllabus, so that while working upon it, targets must be set before. This article explores the key features described in above lines. The purpose of study is to understand properly the impacts of orientalism on our syllabus. Overall strategy of the study is a qualitative research based on extensive documents.